Lifetime Cost Effectiveness of Phenylketonuria Screening Na-tional Program in Iran - Alireza Heidari; Mohammad Arab; Behzad Damari (Tehran University of Medical Sciences, 2021)
Background: Phenylketonuria (PKU) is an autosomal recessive disorder that screening and timely control of this disorder can prevent the adverse effects. Regarding the high prevalence of PKU in Iran, the PKU screening program was started in Iran in 2006. This study was conducted to determine the cost-effectiveness of PKU screening in Iran. Methods: An economic evaluation was performed among screened and treated individuals compared to no screening in 2013. The study population included 1356132 newborns that screened for PKU diagnosis. Lifetime costs, quality-adjusted life year (QALY) gains and incremental cost-effectiveness ratio (ICER) were calculated from the perspective of government. A discount rate of 3% was considered for both QALYs and costs. A one-way sensitivity analysis was used for assessing the robustness of the results. Results: The discounted lifetime cost of intervention and non-intervention were $59528953.8 and $85295501.6 respectively. Therefore, the total estimated cost saving was $25766547.84. PKU screening produces an ICER of $1844420 per QALY gained. Conclusion: Screening and early treatment for PKU is highly cost-effective. Therefore, the screening can improve quality of life of the patients and increase financial saving in health system.